Do experience, education and business plan influence SMEs start-up bank loan? the case of Libya - K.H., Abdesamed (2015)
The financing of small and medium enterprises (SMEs) has been a topic of great interest among both policy-makers and researchers because of the growing importance of SMEs in the economic development around the world. There is also sizeable evidence that SMEs face large growth constraints and have less access to formal sources of external finance such as bank loans, which potentially explains the lack of SMEs' contribution to economic growth. Thus, to understand SMEs' startup financing, we rely on the human capital of owner-manager and SMEs' business strategy to investigate how human capital and business strategy influence SME startup with bank loans. Using survey data based on 76 SMEs in Tripoli and Sabha, the logit model is employed to examine the hypothesized factors. The results show that business plan and owner-manager experiences do influence SMEs' startup bank loan in Libya.